Potential for energy recovery from boundary-layer ingesting actuator disk propulsion - Mutangara, Ngonidzashe E.; Smith, Lelanie; Craig, Kenneth J.; Sanders, Drewan S. (American Institute of Aeronautics and Astronautics (AIAA), 2024)
The theoretical benefits of highly integrated propulsion systems are highlighted herein by assessing the potential for energy recovery utilization using actuator disk propulsion. Decomposing aerodynamic forces into thrust and drag for closely integrated bodies, particularly those employing boundary-layer ingestion, becomes challenging. In this work, a mechanical energy-based approach was taken using the power balance method. This allowed the performance to be analyzed through the mechanical flow power in the fluid domain, disregarding the need for any explicit definition of thrust and drag. Through this, the benefit of boundary-layer ingestion was observed from a wake energy perspective as a decrease in the downstream mechanical energy deposition and associated viscous dissipation. From a propulsion perspective, the reduction in power demand necessary to produce propulsive force indicated the possibility of power savings by utilizing the energy contained within the ingested boundary-layer flow.